Ibermitobase: A search tool for mtDNA population data in the Iberian Peninsula. (December 2015) - Asensio, A.; Marques, S.L.; Ferragut, J.F.; Alvarez, L.; Picornell, A.
Abstract: Human mitochondrial DNA (mtDNA) is routinely analyzed in various disciplines, such as medical genetics, population genetics, and forensic genetics due to several characteristics that make it an invaluable tool, such as high copy number, small size and high substitution rate, apparent lack of recombination and maternal mode of inheritance. In forensic genetics it is highly useful when very limited or degraded DNA is present in a sample. Moreover, owing to its mode of inheritance it enables testing for a putative exclusion scenario in human identification. Statistical interpretation of the results depends on mtDNA population data available. Here we present IBERMITOBASE, an online dynamic database with a compilation of available mtDNA sequences of Spanish and Portuguese populations, where users can easily search and download mtDNA sequences according to different criteria. Currently, the database includes 5364 sequences, 3104 from Spain and 2260 from Portugal. This database is of great value for future studies and can be useful as a review of published data for forensic practice.